2018
DOI: 10.1155/2018/8613209
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Protein Aggregation by Several Antioxidants

Abstract: Amyloid fibril formation is a shared property of all proteins; therefore, model proteins can be used to study this process. We measured protein aggregation of the model amyloid-forming protein stefin B in the presence and absence of several antioxidants. Amyloid fibril formation by stefin B was routinely induced at pH 5 and 10% TFE, at room temperature. The effects of antioxidants NAC, vitamin C, vitamin E, and the three polyphenols resveratrol, quercetin, and curcumin on the kinetics of fibril formation were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 65 publications
3
32
0
Order By: Relevance
“…Therefore, early diagnosis of these disorders, prior to the progression of the pathology, may enhance the chances of success of potential therapeutic approaches ( 28 31 ). Over the past 10 years, many approaches targeting tau aggregates, including small molecules, have been an area of great interest for drug discovery to develop effective disease-modifying therapeutics ( 11 , 32 35 ).…”
mentioning
confidence: 99%
“…Therefore, early diagnosis of these disorders, prior to the progression of the pathology, may enhance the chances of success of potential therapeutic approaches ( 28 31 ). Over the past 10 years, many approaches targeting tau aggregates, including small molecules, have been an area of great interest for drug discovery to develop effective disease-modifying therapeutics ( 11 , 32 35 ).…”
mentioning
confidence: 99%
“…As studied by Hasanbasić et al 31 Regardless of the similarly structured amyloid core with the cross-β structure, this may be explained by an assumption that sequence details and precise arrangement of the subunits in the protofilaments influence aromatic-aromatic π stacking interactions 34 . Indeed, precise arrangement of protofilaments can influence π stacking 35,36 and the same protein can form polymorphic amyloid fibrils, which have specific chemical and biological properties 37,38 .…”
Section: Effect Of Quercetin On Stefin Bfibrillationmentioning
confidence: 97%
“…New experiments (synergistic effect of vitC and polyphenols) were studied by the same methods as described before. The details have been described in papers by Jahic et al 33 for cysC and Hasanbasic, Jahic et al 31 for stB.…”
Section: Comparison Of the Effects Of Vitc And Nac On Kinetics Of Stbmentioning
confidence: 99%
“…In parallel, it was shown that polyphenols from tea lowered the levels of oligomers while enhancing the cell viability in a DAergic substantia nigra/neuroblastoma hybrid cell line known as MES23.5 cells, when they were treated with the combination of MPP+ and α-synuclein monomers or oligomers. Other polyphenols have also shown fibril-destabilizing properties through inhibition of initiation and/or propagation of α-synuclein fibrils in vitro, including quercetin [146,147], curcumin [147][148][149], and its metabolites [150], chlorogenic acid [151], and resveratrol [147]. Interestingly, the oxidized form of quercetin was more efficient at destabilization of human wild-type α-synuclein formation of fibrils and their growth [146].…”
Section: Protein Fibrillationmentioning
confidence: 99%